The epidemiology of heart failure in the general Australian community - study of heart failure in the Australian primary carE setting (SHAPE): methods - Richard Whaddon Parsons; Danny Liew; A. Munro Neville; Ralph G. Audehm; Deepak Haikerwal; Peter Piazza; Kevin Lim; Andrew P. Sindone (BMC, 2020)
Abstract Background There is a paucity of information on the epidemiology of heart failure (HF) in Australia. The Study of Heart failure in the Australian Primary carE setting (SHAPE) study aims to estimate the prevalence and annual incidence of HF in the general Australian community and to describe the demographic and key clinical profile of Australians with HF. Methods We undertook a retrospective cohort study based on analysis of non-identifiable medical records of adult patients cared for at 43 general practices between 1 July 2013 and 30 June 2018. Data were extracted from coded (diagnosis, pathology and prescription fields) and uncoded fields (clinical notes) in the medical records. The latter searches of free text looked for common synonyms relevant to HF. The population was stratified into three groups based on a hierarchy of selection criteria: (1) definite HF, (2) probable HF and (3) possible HF. The prevalence and annual incidence of HF were calculated, along with 95% confidence intervals. Results The practices provided care to 2.3 million individual patients over the five-year study period, of whom 1.93 million were adults and 1.12 million were regular patients. Of these patients 15,468 were classified as having 'definite HF', 4751 as having 'probable HF' and 33,556 as having 'possible HF'. A further 39,247 were identified as having an aetiological condition associated with HF. A formal HF diagnosis, HF terms recorded as text in the notes and HF-specific medication were the most common methods to identify 'definite' HF patients. Typical signs and symptoms in combination with a diuretic prescription was the most common method to identify 'probable HF' patients. The majority of 'possible' HF patients were identified by the presence of 2 or more of the typical signs or symptoms. Dyspnoea was the commonest recorded symptom and an elevated jugular venous pressure the commonest recorded sign. Conclusions This novel approach to undertaking retrospective research of primary care data successfully analysed a combination of coded and uncoded data from the electronic medical records of patients routinely managed in the GP setting. SHAPE is the first real-world study of the epidemiology of HF in the general Australian community setting.